Transfer RNA genes in the cap-oxil region of yeast mitochondrial DNA. - Berlani, R E (1980)
A cytoplasmic "petite" (rho-) clone of Saccharomyces cerevisiae has been isolated and found through DNA sequencing to contain the genes for cysteine, histidine, leucine, glutamine, lysine, arginine, and glycine tRNAs. This clone, designated DS502, has a tandemly repeated 3.5 kb segment of the wild type genome from 0.7 to 5.6 units. All the tRNA genes are transcribed from the same strand of DNA in the direction cap to oxil. The mitochondrial DNA segment of DS502 fills a sequence gap that existed between the histidine and lysine tRNAs. The new sequence data has made it possible to assign accurate map positions to all the tRNA genes in the cap-oxil span of the yeast mitochondrial genome. A detailed restriction map of the region from 0 to 17 map units along with the locations of 16 tRNA genes have been determined. The secondary structures of the leucine and glutamine tRNAs have been deduced from their gene sequences. The leucine tRNA exhibits 64% sequence homology to an E. coli leucine tRNA.